Sistem Informasi Perjalanan Dinas Berbasis Web Di DP3AP2KB Kabupaten Banggai Kepulauan - Heriyanto Sahidu (Akademi Manajemen Informatika dan Komputer Luwuk Banggai, 2021)
Making an official travel order (SPPD) in the DP3AP2KB Banggai Regency is still done manually, namely using the Microsoft Word application which must be done every time you make an official travel order (SPPD). then we need a system that is able to manage official travel orders (SPPD) within the DP3AP2KB Banggai Regency. The research method in developing a web-based official travel information system at DP3AP2KB Banggai Islands Regency uses a qualitative method approach. Sources of qualitative data were obtained through observations and interviews with DP3AP2KB Banggai Islands Regency as well as Literature Studies related to the theories that support the process of preparing Minor Papers. The results obtained in the study, namely, a web-based official travel information system at DP3AP2KB Banggai Islands Regency can make it easier for employees to make official trips in managing official travel administration and make it easier for policy makers to unify the official travel process for employees. With the existence of a web-based official travel information system at DP3AP2KB Banggai Islands Regency, it is hoped that it can help the process of making official travel administration to be more effective and efficient